2022
DOI: 10.3389/fpubh.2022.954416
|View full text |Cite
|
Sign up to set email alerts
|

Determining the association between different living arrangements and depressive symptoms among over-65-year-old people: The moderating role of outdoor activities

Abstract: BackgroundChina is presently facing the challenge of meeting enormous health demands because of its rapidly aging society. Enrolling older persons in eldercare institutions is a helpful alternative for relieving family caregivers and promoting healthy aging. However, changes in the living environment may negatively affect the mental health of the elderly.ObjectiveTo explore the association between different living arrangements and depressive symptoms among over-65-year-old people in China and the moderating ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The opposite in uences of living close to their children and living far from them explain why solitary living does not signi cantly in uence senior urban residents' mental health. [11]conclusions. Their research found that seniors who lived alone were more depressed.…”
Section: Urban-rural Differencesmentioning
confidence: 91%
“…The opposite in uences of living close to their children and living far from them explain why solitary living does not signi cantly in uence senior urban residents' mental health. [11]conclusions. Their research found that seniors who lived alone were more depressed.…”
Section: Urban-rural Differencesmentioning
confidence: 91%
“…Wang and Wang (2018) concluded from a survey of 386 university students that being active in a natural environment significantly and negatively predicted depressed mood. Xu et al (2022) conducted a study on the relationship between living arrangements and depressive symptoms in 12,200 elderly people, and Mechanisms by which pro-nature physical activity antagonizes psychological stress through MGBA. 10.3389/fpsyg.2023.1143827 Frontiers in Psychology 07 frontiersin.org found that outdoor physical activities had a good effect on reducing depressive symptoms in the elderly.…”
Section: Inspiration For Exercise Interventions For Psychological Str...mentioning
confidence: 99%
“…Regarding the association between living arrangements and older adults' health outcomes, although mixed results have been documented in a variety of social contexts, in China, where there is a strong tradition of filial piety and an expectation of sons providing care to older adults, empirical findings largely corroborated that co-residence had a positive impact on older adults' health. In general, older adults who lived with adult children were found to report better SRH, a lower likelihood of having activity of daily living (ADL) disabilities, and were less likely to feel lonely or depressed ( 4 , 17 19 ). Scholars also observed that Chinese older adults who lived with family members had greater odds of reporting good quality of sleep and a longer duration of sleep ( 20 ).…”
Section: Literature Reviewmentioning
confidence: 99%